Atsar Al-Tholaq Fi Al Fiqh Al Islami Wa Alqanun Al Indonisi (Dirasah Muqaranah Maydaniyah Fi Madinati Solo) - Saleh Abdat, Hanan (2012)
Divorce is an old social problem and it is a common phenomenon in all societies. Now days, it seems to be increasing rapidly in Indonesia in general and especially in the city of Solo. There is no doubt that divorce has moral, financial and social effects. The moral and financial effects of divorce come in five things: iddat, the period in which the widow is not allowed remarrying, composition given to a divorced woman, alimony, breastfeeding and the nursery. Islam has taken into account those effects so it binds duties and maintains rights. It emphasized on the importance of duties and rights and not to take them for guarantee. But today with the ability to play on the law of personal status concerning divorce in Indonesia and the ignorance to the provisions of Islamic jurisprudence, a lot of problems and differences on divorce and its issues have increased. The researcher, when writing this study, has talked in both theory and application. She followed the inductive approach to the provisions of Islamic jurisprudence and the methodology of criticism compared to the laws of personal status on the Marriage Law in Indonesia No. 1 of 1974 in the section of divorce. She compared them to the applications of Indonesian Muslim society and she supported that with a field study. She also revealed the data issued by the Religious Court related to divorce issues in Solo city. To sum up, we must fight against the indirect ways of playing with the law in the Indonesian Marriage Law No. 1 of 1974 especially in the section of divorce. Also, organizing the activities of institutions and courses related to the family in educating the community about their rights and duties that go with the spirit of Islamic law.